2014
DOI: 10.1177/1087057114520973
|View full text |Cite
|
Sign up to set email alerts
|

Assay Development and High-Throughput Screening for Inhibitors of Kaposi’s Sarcoma–Associated Herpesvirus N-Terminal Latency-Associated Nuclear Antigen Binding to Nucleosomes

Abstract: Kaposi's sarcoma associated herpesvirus (KSHV) has a causative role in several human malignancies, especially in immunocompromised hosts. KSHV latently infects tumor cells and persists as an extrachromosomal episome (plasmid). KSHV latency-associated nuclear antigen (LANA) mediates KSHV episome persistence. LANA binds specific KSHV sequence to replicate viral DNA. In addition, LANA tethers KSHV genomes to mitotic chromosomes to efficiently segregate episomes to daughter nuclei after mitosis. N-terminal LANA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…While non-stoichiometric inhibitors constitute a major component of raw HTS hit lists [54] and confirmed stoichiometric inhibitors are relatively few, [55,73] this is not surprising if truly novel inhibition modes are sought. It is simply not realistic to assume that there are thousands of truly stoichiometric and specific inhibitors against unprecedented targets in standard screening libraries, which are frequently fed with compounds from earlier medicinal chemistry efforts against well-established target classes.…”
Section: Managing Non-stoichiometric Inhibition By Integrated Lead Fimentioning
confidence: 95%
See 2 more Smart Citations
“…While non-stoichiometric inhibitors constitute a major component of raw HTS hit lists [54] and confirmed stoichiometric inhibitors are relatively few, [55,73] this is not surprising if truly novel inhibition modes are sought. It is simply not realistic to assume that there are thousands of truly stoichiometric and specific inhibitors against unprecedented targets in standard screening libraries, which are frequently fed with compounds from earlier medicinal chemistry efforts against well-established target classes.…”
Section: Managing Non-stoichiometric Inhibition By Integrated Lead Fimentioning
confidence: 95%
“…The efficacy of this approach is demonstrated by an extreme case study in which the hit list was completely annihilated by such filtering. [73] This was without doubt disappointing for the investigators but much preferable to further, wasted efforts as in the notorious case of the presumed sirtuin activator resveratrol. [94] However, as most of the assays focus on just one type of non-stoichiometric inhibition, it is hardly possible to identify each and every of the many different mechanisms.…”
Section: Experimental Identification Of Nonstoichiometric Inhibitors mentioning
confidence: 98%
See 1 more Smart Citation
“…An attempt to identify specific inhibitors of KSHV was recently conducted focused on small molecules with the ability to displace the LANA peptide from the acidic patch [19]. High-throughput screening of large chemical libraries with more than 350 000 compounds identified many small molecules that prevented LANA binding to the nucleosome.…”
Section: Npmentioning
confidence: 99%
“…[7] LANAb inds to the acidic patch, an egatively charged region on the nucleosome surface formed by acidic residues from H2A and H2B. [1a, 2c] A2 0residue peptide derived from the LANA N-terminus binds tightly (K D = 0.16 mm)t on ucleosomes,i n agreement with previous studies using longer fragments [21] ( Figure S6 A). TheL ANAp eptide (2 kDa) was added in fivefold molar excess to ad ilute solution of H2A-labeled nucleosomes from the same batch as the sample used for assignment, followed by sedimentation into the rotor.C omparison of the remaining supernatant and pure LANA peptide solution by NMR spectroscopy suggested that the peptide had been successfully co-sedimented with the nucleosome (Figure S6 B).…”
mentioning
confidence: 94%